Calculation of renewable energy hosting capacity of distribution network based on multi strategy improved adaptive manta ray foraging optimization - Yuan, Zhiyong; Xu, Min; Tao, Yigang; Li, Min; Guo, Zuogang; Zhang, Juncheng (Frontiers in Energy Research, 2023)
With the increasing penetration of renewable energy in the distribution network, however, due to the randomness and volatility of renewable energy output, the large-scale grid connection of renewable energy will bring challenges to the safe and stable operation of the distribution network. The calculation of renewable energy hosting capacity of distribution network is not only beneficial to the construction of renewable clean and low-carbon power system, but also of great significance for the planners of power grid to carry out renewable energy planning. Renewable energy hosting capacity calculation involves many constraints, including a large number of nonlinear constraints, and the hosting capacity calculation model is very complex, lacking efficient solution algorithm. Aiming at the existing problems, after fully considering power quality, relay protection and thermal stability inspection, the index evaluation system and calculation model of renewable energy hosting capacity of distribution network are established, and multi strategy improved adaptive manta ray foraging optimization algorithm(MSAMRFO) is proposed to solve the hosting capacity model. Finally, an example is given to demonstrate the validity of the model and method proposed in this paper.